ANALISIS KINERJA KEUANGAN PERUSAHAAN DITINJAU DARI RENTABILITAS, LIKUIDITAS, SOLVABILITAS (STUDI PADA PT. MISWAK UTAMA) - Indriani Rafika Sari; Ufi Rumefi; Rohman Dijaya; Ersa Zabrina; Akhmad Tajuddin (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2024)
The purpose of this study is to analyse the financial performance of the company in terms of profitability, liquidity, and solvency in 2015-2019 at PT Miswak Utama. The data analysis method in this study is quantitative descriptive. PT Miswak Utama's financial statements were analysed in terms of profitability, liquidity, and solvency, which were then compared with industry standard ratios. The results showed that the profitability ratio, calculated from the gross profit margin and net profit margin, indicated that PT Miswak Utama was in poor condition, except in 2015, when it had a fairly high net profit. Furthermore, the liquidity ratio calculated from the current ratio and quick ratio also showed that PT Miswak Utama was in a poor condition because it was unable to pay its current liabilities. The solvency ratio calculated from the debt to asset ratio and debt to equity ratio also showed that PT Miswak Utama was in a poor condition because it was unable to guarantee the company's debts, which would result in a lack of trust from creditors.